The Electricity Security in South Africa: Analysing Significant Determinants to the Grid Reliability - Ateba, Benedict Belobo; Prinsloo, Johannes Jurgens (International Journal of Energy Economics and Policy, 2018)
South Africa has been suffering from low electricity supply for decades now, dating back to the first occurrence during 1983. Another crisis struck by the fall of 2007, which shocks from the crisis still affect the economic growth. The country’s fossil fuels, which serve as a major contributor to its electricity generation, are depleted by 1% every year. Other determining variables such as increases in domestic consumption and industrial intensity as domestic and industrial consumption rise, increase in coal prices, drop in the production volumes of coal, depreciation in machinery remain continuous dangers to the future reliability of supply of the grid. This has led to inflation of consumer prices, as end users’ future access to adequate electricity supply is not guaranteed. This paper aimed at determining the steadfastness of the South African electricity grid in meeting consumers’ demands. A quantitative research design was employed. A multiple time series research method utilising secondary data from key determining variables to electricity supply from the first quarter of 1998 to the last quarter of 2015 was employed in this study. The Eviews statistical software was employed to obtain regression probabilities through the multiple Ordinary Least Square model (OLS) specifications. The Engle-Granger approach was used to establish whether or not co-integration exists between the independent and the dependent variables. The co-integration analysis reflects that there is a significant long-term relationship between the independent and the dependent variables. Keywords: Electricity security, supply determinants, grid sustainability JEL Classification: Q47 DOI: https://doi.org/10.32479/ijeep.6864